ISSUES ON THE APPLICATION OF A QUALITY-RISK MANAGEMENT SYSTEM IN A HEALTHCARE SERVICES PROVIDER UNIT - CONSTANTIN MILITARU; LEONARDO VOINESCU (Journal of Engineering Studies and Research)
A medical service, as a public service, is composed of a provider represented by the medical staff and a framework that carries out their work. Therefore, a qualitative management of services must be taken into account, on the one hand by the quality of care itself, and on the other hand by how the resource material is managed throughout the services provided. Fortunately, quality and risk management systems concepts are becoming more widely used in their speech, by the responsible with those services at European and national level. A quality medical service can be attained through a rigorous and effective management of the quality of medical care itself, and through increased quality of human resources and materials involved and ensuring health and reduce the risks of treatment/ care patients. The authors present in brief a model of risk assessments and risk classification in a medical unit.